Damage tolerant design of additively manufactured metallic components subjected to cyclic loading: State of the art and challenges - Zerbst, Uwe; Bruno, Giovanni; Buffière, Jean-Yves; Wegener, Thomas; Niendorf, Thomas; Wu, Tao; Zhang, Xiang; Kashaev, Nikolai; Meneghetti, Giovanni; Hrabe, Nik; Madia, Mauro; Werner, Tiago; et al. (Progress in materials science, 2021)
Undoubtedly, a better understanding and the further development of approaches for damage tolerant component design of AM parts are among the most significant challenges currently facing the use of these new technologies. This article presents a thorough overview of the discussion at an international workshop on the topic. It aims to provide a review of the parameters affecting the damage tolerance of parts produced by additive manufacturing (shortly, AM parts) with special emphasis on the process parameters intrinsic to the AM technologies, the resulting defects and the residual stresses. Based on these aspects, basic concepts are reviewed and critically discussed specifically for AM materials:-Criteria for damage tolerant component design;-Criteria for the determination of fatigue and fracture properties;-Strategies for the determination of the fatigue life in dependence of different manufacturing conditions;-Methods for the quantitative characterization of microstructure and defects;-Methods for the determination of residual stresses;-Effect of the defects and the residual stresses on the fatigue life and behaviour.We see that many of the classic concepts need to be expanded in order to fit with the particular microstructure (grain size and shape, crystal texture) and defect distribution (spatial arrangement, size, shape, amount) present in AM (in particular laser powder bed fusion). For instance, 3D characterization of defects becomes essential, since the defect shapes in AM are diverse and impact the fatigue life in a different way than in the case of conventionally produced components. Such new concepts have immediate consequence on the way one should tackle the determination of the fatigue life of AM parts; for instance, since a classification of defects and a quantification of the tolerable shapes and sizes is still missing, a new strategy must be defined, whereby theoretical calculations (e.g. finite element modeling) allow determining the maximum tolerable defect size, and non-destructive testing (NDT) techniques are required to detect whether such defects are indeed present in the component. Such examples show how component design, damage and failure criteria, and characterization (and/or NDT) become for AM parts fully interlinked. We conclude that the homogenization of these fields represents the current challenge for the engineer and the materials scientist.